EFEKTIVITAS PENDEKATAN SCIENTIFIC DENGAN METODE OBSERVASI DAN DISKUSI DALAM MENINGKATKAN CAPAIAN BELAJAR DAN KINERJA SISWA KELAS VII SMP KRISPA SILIAN - Inggrit Octavia Akay; Djeli Alvi Tulandi; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
The first step to learn science is through observation and measurement as a part of the observation. The research was conducted with the aim to improve the processes and student learning outcomes by implementing the teaching through the application of a scientific approach to the method of observation and discussion on the subject of "object IPA and observations". The research was conducted on a class VII SMP Negeri 1 Airmadidi 2015-2016 school year the number of students 30 people. The study design used is a Class Action Research or Classroom Action Research model of John Elliot. The data analysis technique used is descriptive analysis techniques, where the data described is data about students' ability to master scientific concepts and data on student engagement during the learning process takes place. To obtain the necessary data in this study used the instrument in the form of Student Worksheet (LKS) and tests to determine the level of student mastery of concepts. Result reflections 1 suggested need to proceed to the second cycle because of the 30 students there are 17 students who have not been thoroughly studied. Through learning activities and teaching the second cycle showed that all students have been thoroughly studied and an increase in average student learning outcomes of 64.83 (first cycle) to 74.67 (second cycle). Results of this study concluded that the application of a scientific approach to the method of observation and discussion on the objects of material science and observations can improve the process and the achievements of students of class VII SMP Negeri 1 Airmadidi.